Gender and the Violence(s) of War and Armed Conflict More Dangerous to be a Woman? - Banwell, Stacy (Emerald Publishing, 2020)
Drawing on historical and contemporary case studies, Gender and the Violence(s) of War and Armed Conflict delves into visual as well as text-based materials to unpack gender-based violence(s) perpetrated and experienced by both genders within and beyond the conflict zone.Considering examples of old and new wars ranging from the Holocaust, the 1971 Liberation War in Bangladesh; and the armed conflicts in the DRC, Iraq, Syria and Darfur, this book uncovers sexualised, genocidal and reproductive violence against both genders. Crucially, the author showcases examples of male victimisation, and thus redresses gaps within the literature. In particular, as part of an original gendered analysis of the war on terror, Banwell unpacks women's involvement in sexual violence against male prisoners at Abu Ghraib.By going beyond instances of interpersonal violence, and looking additionally at structural forms of gender-based violence, state violence, institutional violence and climate variability, this book broadens our understanding of both the causes and consequences of modern conflicts. Through her critique of gender essentialism, the author challenges gendered notions of who 'is dangerous' and who is 'in danger' during war/armed conflict. Eclectic in its approach, and multi-disciplinary in scope, Banwell's text is illuminating reading for academics, students and professionals working with war-affected populations.